Estimation of Potential Gold Mineral (Au) with A Resistivity Approach - Akroma Hidayatika; Arif P Prabowo; Syamsurijal Rasimeng; Medi K Putri; Suharno (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2021)
This research was conducted in Pesisir Barat Regency. This study aims to calculate the estimated potential gold mineral content Gold is formed as a result of the residual solution of magma being uplifted and deposited at high temperatures and pressures. The gold mineral in this area is a ) low sulphidation hydrothermal gold deposit epithermal type (in the form of quartz veins, with carrier minerals containing metals and non-metals. This research uses resistivity method. Interpretation is done by analyzing the resistivity 2D cross section. The interpretation of the gold mineralization zone is associated with the source rock (volcanic) which has a resistivity value of 500Ω.m. Based on resistivity modeling, assuming the source rock is an andesitic-basaltic igneous rock with a density of 2.8 g/cm3 and a maximum depth of 30 meters, it is estimated that the mineral content (Au) in this research location is in the range of (0,3 – 1,5) tons.